2021
DOI: 10.1016/j.sjbs.2021.06.028
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16, LRP1 and TRPM8 genetic polymorphisms are risk factor for Pakistani migraine patients

Abstract: Background Migraine is a chronic neurovascular condition characterized by recurring attacks of pulsating headaches. Genome-wide association studies (GWAS) identified many potential loci associated with migraine. To check the association of polymorphisms of PRDM16 (rs2651899), LRP1 (rs11172113), and TRPM8 (rs10166942) with migraine, the first time a case-control study was conducted in understudied Pakistani population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Additionally, a study by Xian et al (2017) found that phosphorylation of LDL-related protein 1 (LRP-1) on the macrophage surface could also increase ABCA1 protein expression by activating the LRP-1/SHC1/PI3K/AKT/PPAR-γ/LXR axis [ 78 ]. The rs11172113*C is a common variant of LRP1 that could cause splice site alteration in one of the gene’s exon-intron junctions [ 79 ]. This could result in LRP-1 structural change [ 79 ], which could potentially impair the protein activity.…”
Section: Discussion and Narrative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study by Xian et al (2017) found that phosphorylation of LDL-related protein 1 (LRP-1) on the macrophage surface could also increase ABCA1 protein expression by activating the LRP-1/SHC1/PI3K/AKT/PPAR-γ/LXR axis [ 78 ]. The rs11172113*C is a common variant of LRP1 that could cause splice site alteration in one of the gene’s exon-intron junctions [ 79 ]. This could result in LRP-1 structural change [ 79 ], which could potentially impair the protein activity.…”
Section: Discussion and Narrative Synthesismentioning
confidence: 99%
“…The rs11172113*C is a common variant of LRP1 that could cause splice site alteration in one of the gene’s exon-intron junctions [ 79 ]. This could result in LRP-1 structural change [ 79 ], which could potentially impair the protein activity. Since our findings showed that both rs1412444*T ( LIPA ) and rs11172113*C ( LRP1 ) increased CHD risk 1.02-fold ( Table S2 ), we hypothesize that the underlying mechanisms might be related to reduced lipase A enzyme expression and structural variation of the LRP-1 protein that renders it less functional.…”
Section: Discussion and Narrative Synthesismentioning
confidence: 99%
“…Moreover, the rs12472151 , rs11562975 , and rs28901637 polymorphisms of the TRPM8 gene were associated with metabolic syndrome, obesity, and cholesterol levels [ 138 , 139 , 140 ]. Variants at TRPM8, rs10166942 , and rs2362290 have been related to slower colonic transit rates, increased risk of irritable bowel syndrome, and chronic migraine [ 141 , 142 ].…”
Section: Pharmacogenomics Of Receptorsmentioning
confidence: 99%
“…Rs2651899 of PRDM16 showed associations in the Women's Genome Health Study (WGHS) with migraine compared to non-migraineurs and also with migraine compared to non-migraine type headache [44]. A replication study on a Chinese population supported a role for rs2651899 as a risk factor in migraine without aura regardless of gender [45] and its role was also demonstrated in two North Indian, a Chinese Han, a Spanish, a Swedish, and a Pakistani population [46][47][48][49][50][51]. A recent meta-analysis also demonstrated an association between rs2651899 and migraine risk [52].…”
Section: Plos Onementioning
confidence: 99%